2017
DOI: 10.1016/j.cell.2017.07.023
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 Maintains Microglial Metabolic Fitness in Alzheimer’s Disease

Abstract: Summary Elevated risk of developing Alzheimer’s disease (AD) is associated with hypomorphic variants of TREM2, a surface receptor required for microglial responses to neurodegeneration, including proliferation, survival, clustering and phagocytosis. How TREM2 promotes such diverse responses is unknown. Here, we find that microglia in AD patients carrying TREM2 risk variants and TREM2-deficient mice with AD-like pathology have abundant autophagic vesicles, as do TREM2-deficient macrophages under growth factor l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
797
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 873 publications
(841 citation statements)
references
References 56 publications
41
797
1
2
Order By: Relevance
“…Moreover, reduced TREM2 is associated with increased autophagy in a mouse model for AD (Ulland et al . ). Hence, the effects of reduced TREM2 on the autophagy pathway and Aβ accumulation in brains of HIV+ individuals warrant future investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, reduced TREM2 is associated with increased autophagy in a mouse model for AD (Ulland et al . ). Hence, the effects of reduced TREM2 on the autophagy pathway and Aβ accumulation in brains of HIV+ individuals warrant future investigation.…”
Section: Discussionmentioning
confidence: 97%
“…Several sequence variants associated with TREM2 cause neurodegeneration via a loss of function (Kleinberger et al , , ; Schlepckow et al , ; Ulland et al , ; Song et al , ). Sequence variants of TREM2 affect a multitude of functions including chemotaxis, migration, survival, binding of phospholipids and ApoE, proliferation, survival, and others (Kleinberger et al , , ; Atagi et al , ; Bailey et al , ; Wang et al , ; Yeh et al , ; Mazaheri et al , ; Ulland et al , ). Strikingly, a loss of TREM2 function locks microglia in a homeostatic state (Krasemann et al , ; Mazaheri et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…More interesting, recent studies found a novel microglia cell type associated with neurodegenerative diseases (DAM cells) using single‐cell RNA‐seq technology, which displayed a unique capability to clear Aβ (Keren‐Shaul, Spinrad, Weiner, Matcovitch‐Natan, & Dvir‐Szternfeld, 2017). Furthermore, another group also found glial cells in patients with AD bearing TREM2 variants, and Trem2 ‐deficient mice have a greater abundance of autophagic vesicle accumulation and an AD‐like pathology (Ulland, Song, Huang, Ulrich, & Sergushichev, 2017). In a mechanical manner, they reported that these specific glial cells are activated sequentially by both Trem2‐independent and Trem2‐dependent pathways, which involved in mTOR‐mediated autophagy and metabolic biosynthetic pathways (Ulland et al., 2017).…”
Section: The Important Role Of Protein Synthesis Pathways In Cancer Amentioning
confidence: 99%
“…Furthermore, another group also found glial cells in patients with AD bearing TREM2 variants, and Trem2 ‐deficient mice have a greater abundance of autophagic vesicle accumulation and an AD‐like pathology (Ulland, Song, Huang, Ulrich, & Sergushichev, 2017). In a mechanical manner, they reported that these specific glial cells are activated sequentially by both Trem2‐independent and Trem2‐dependent pathways, which involved in mTOR‐mediated autophagy and metabolic biosynthetic pathways (Ulland et al., 2017). These findings together suggest that the disturbance of proteostasis in glial cells mediated by the TREM2‐mTOR axis may lead to further Aβ accumulation.…”
Section: The Important Role Of Protein Synthesis Pathways In Cancer Amentioning
confidence: 99%